The Concept of the Perfect Human (al-Insan al-Kamil) in Islamic Education According to al-Ghazali and Its Implementation in Indonesian Islamic Higher Education - Iskandar, Sofwan; Saepudin, Didin; Husaini, Adian; Syafrin, Nirwan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
Abstract Human perfection is intrinsically linked to virtues (al-fadhā’il), namely wisdom (al-hikmah), courage (al-syaja‘ah), temperance (al-‘iffah), and justice (al-‘adalah). Through these virtues, individuals attain true happiness, which al-Ghazali in Ma‘arij al-Quds describes as beholding God in the hereafter or attaining divine knowledge (ma‘rifat al-Bāri). This study has three main objectives: first, to explain the concept of the Perfect Human (al-insan al-kamil); second, to analyze al-Ghazali’s perspective on this concept within Islamic education; and third, to examine its implementation at STIT Insan Kamil, Bogor City. The research employs qualitative methods in a descriptive, analytical, implementative, and evaluative approach, drawing on interviews with students, lecturers, and staff, supported by institutional data. For al-Ghazali, the Perfect Human is one who balances morality, intellect, and righteous deeds, achieving harmony in relationships with God, fellow human beings, and the universe. Education should therefore go beyond worldly ambitions and guide individuals toward closeness to God. At STIT Insan Kamil, this concept is applied, although Qur’an memorization targets remain less optimal and require continuous improvement. Abstrak Kesempurnaan manusia erat kaitannya dengan kebajikan (al-fadhā’il), yaitu kebijaksanaan (al-hikmah), keberanian (al-syaja‘ah), kesederhanaan (al-‘iffah), dan keadilan (al-‘adalah). Melalui kebajikan tersebut manusia mencapai kebahagiaan sejati, yang oleh al-Ghazali dalam Ma‘arij al-Quds digambarkan sebagai memandang Allah di akhirat atau mengenal-Nya (ma‘rifat al-Bāri). Penelitian ini memiliki tiga tujuan utama, yaitu menjelaskan konsep insan kamil (al-Insan al-Kamil), menganalisis pandangan al-Ghazali tentang konsep ini dalam pendidikan Islam, serta mengkaji implementasinya di STIT Insan Kamil Kota Bogor. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, analitis, implementatif, dan evaluatif melalui wawancara dengan mahasiswa, dosen, dan tenaga kependidikan, serta ditunjang oleh telaah data kelembagaan. Bagi al-Ghazali, insan kamil adalah manusia yang mampu menjaga keseimbangan antara akhlak, intelektualitas, dan amal saleh sehingga tercapai keharmonisan hubungan dengan Allah, dengan sesama manusia, dan dengan alam semesta. Pendidikan karena itu tidak hanya berorientasi pada status duniawi atau kekayaan, tetapi bertujuan mendekatkan individu kepada Allah. Di STIT Insan Kamil, konsep ini diterapkan meskipun target hafalan al-Qur’an masih belum optimal dan terus ditingkatkan. How to Cite: Iskandar S., Saepudin, D., Husaini, A., & Syafrin, N. (2025). The Concept of the Perfect Human (al-Insan al-Kamil) in Islamic Education According to al-Ghazali and Its Implementation in Indonesian Islamic Higher Education. TARBIYA: Journal of Education in Muslim Society, 12(1), 97-114. doi:10.15408/tjems.v12i1.46553.